Bastard Culture! How User Participation Transforms Cultural Production - Schäfer, Mirko Tobias (MediaMatters, 2011)
In the wake of the recent far-reaching changes in the use and accessibility of technology in our society, the average person is far more engaged with digital culture than ever before. They are not merely subject to technological advances but actively use, create, and mold them in everyday routines-connecting with loved ones and strangers through the Internet and smart phones, navigating digital worlds for work and recreation, extracting information from vast networks, and even creating and customizing interfaces to best suit their needs. In this timely work, Mirko Tobias Schäfer delves deep into the realities of user participation, the forms it takes, and the popular discourse around new media. Drawing on extensive research into hacking culture, fan communities, and Web 2.0 applications, Schäfer offers a critical approach to the hype around user participation and exposes the blurred boundaries between industry-driven culture and the domain of the user.